2018
DOI: 10.4236/ce.2018.914165
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory Factor Analysis on the Sub-Construct of Teaching Presence’s in the Community of Inquiry

Abstract: This study aims to reexamine the reliability and validity of three sub-constructs in measuring the level of teaching presence from one of the essential elements in the Community of Inquiry model. The measurement consists of 13 items which are online instructor capability; design and organization, facilitation, and direct instruction. A total of 1938 respondents from a faculty in a public university in Malaysia were selected in the data collection. A cross-sectional survey was applied via online survey and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The synchronized nature of online discussions was deemed inappropriate in meeting every individual's needs in a group. A similar situation was discussed by Simpson (2018), stating that students who coped well with the flow of discussion would inadvertently pose a threat to others who may feel excluded and lose self-confidence (Nasir et al, 2018a;Nasir et al, 2018b). Therefore, teachers were encouraged to explain the learning schedule prior to class hours and provide the necessary materials to prepare in advance, as students mostly relied on self-study to overcome the challenges in online classes (Rovai & Downey, 2010), especially during the pandemic (Wisneski et al, 2017).…”
Section: Utilization Of Technological Advancementmentioning
confidence: 80%
See 1 more Smart Citation
“…The synchronized nature of online discussions was deemed inappropriate in meeting every individual's needs in a group. A similar situation was discussed by Simpson (2018), stating that students who coped well with the flow of discussion would inadvertently pose a threat to others who may feel excluded and lose self-confidence (Nasir et al, 2018a;Nasir et al, 2018b). Therefore, teachers were encouraged to explain the learning schedule prior to class hours and provide the necessary materials to prepare in advance, as students mostly relied on self-study to overcome the challenges in online classes (Rovai & Downey, 2010), especially during the pandemic (Wisneski et al, 2017).…”
Section: Utilization Of Technological Advancementmentioning
confidence: 80%
“…Leow et al (2020) reported that online discussions impacted students differently. For example, the indirect exchange of information and experiences could induce a sense of belonging and communal engagement (Nasir et al, 2018a;Nasir et al, 2018b), whereas an indirect meeting absolved students' fear in contributing information. Nevertheless, some students could not realize these values in situations where the discussion proved too overwhelming, emotional, or lacked professionalism.…”
Section: Teaching and Learning From Homementioning
confidence: 99%
“…Despite the advantage of technology, online learning and student conversation have diverse effects, with inert student engagement in virtual classes (Simpson, 2018). By experiencing a lack of self-confidence, online classes are perceived as improper in meeting discussions in large groups of individuals (Nasir et al, 2018a;Nasir et al 2018b). This is due to the student's fear in virtual learning or discussion for exchange information and experiences indirectly compared to a direct school class.…”
Section: Issues In Virtual Learningmentioning
confidence: 99%
“…Thus, capturing pupils' interest and motivating them are important in the vocabulary learning process. When they stop enjoying lessons, there is a tendency for them to learn less in class (Nasir, Surat, Maat, Abd Karim, & Daud, 2018;Nasir, Mansor, & Rahman, 2018). Afzal (2019) also found that the majority of teachers still employ the traditional teaching methods which are outdated.…”
Section: Introductionmentioning
confidence: 99%